Why some places are left-behind: urban adjustment to trade and policy shocks - Venables, AJ (Oxford University Press, 2021)
Economic adjustment to trade and policy shocks is hampered by the fact that some sectors tend to cluster, so are hard to initiate in new places. This can give rise to persistent spatial disparities between cities within a country. The paper sets out a two-sector model in which cities divide into those producing tradable goods or services subject to agglomeration economies, and those only producing non-tradables for the national market. If import competition destroys some established tradable sectors, then affected cities fail to attract new tradable activities and switch to just produce non-tradables. Full employment is maintained (we assume perfect markets and price flexibility) but disparities between the two types of cities are increased. All non-tradable cities experience real income loss, while remaining tradable cities boom. The main beneficiaries are land-owners in remaining tradable cities, but there may be aggregate loss as the country ends up with too many cities producing non-tradables, and too few with internationally competitive activities. Fiscal policy has opposite effects in the two types of cities, with fiscal contraction causing decline in cities producing non-tradables, increasing activity in cities producing tradable goods, widening spatial disparities, and in the process increasing the share of rent in the economy.